INTERAKSI SOSIAL DALAM BELAJAR IPS PESERTA DIDIK PADA KELAS VII B DI SMPN 1 SUNGAI RAYA - Seselia, Seselia; Aminuyati, Aminuyati; Anasi, Putri Tipa (Universitas Tanjungpura, 2023)
This study aims to identify the factors and forms of social interaction of class VII B students at SMPN 1 Sungai Raya, Kubu Raya Regency. The research method in this study is qualitative. Research data is sourced from primary and secondary data and collected using observation, interviews, and documentation. In addition, these techniques were assisted by data collection tools in the form of observation guides, interview guides, and documentation guides. The data that has been collected is analyzed starting from the data reduction stage, data display, and drawing conclusions. Based on the results, social interaction in social studies learning in class VII B at SMPN Sungai Raya occurs because there is a good relationship between fellow students as well as students and teachers. In addition, students have a sense of mutual help among each other, have discipline in learning that is supported by a good learning environment, and have good cooperation in learning. Conclusion the factor of social interaction in social studies learning in class VIIB at SMPN 1 Sungai Raya is that students have a desire to learn and prepppare themselves to start learning. Student can create good relationship with teachers and friends, are polite and respectful to teacher and each other. The form of social interaction in social studies learning in class VIIB at SMPN 1 Sungai Raya is in the form of cooperation with class VIIB student at SMPN 1 Sungai Raya with group divisions basedbon seats and the form of task search will be divided.